Pelatihan Balance Exsercise Untuk Menjaga Keseimbangan Pada Lansia di Kelurahan Pondok Ranggon - Yuli Astuti; Neneng Elviana; Uum Safari; Dhien Novita Sani; Nova Riani; Irsan (Sagamedia Indo Press, 2022)
Background: Elderly (elderly) is a group of people with a special age, namely above 60 years, both men and women who have independence or even still need the help of others. The aging process is a human process towards the end of life with the support of a decrease in the ability of the system in the body. Elderly people often experience changes in their bodies over time, the most significant changes in the elderly are those that occur in the musculoskeletal system, especially the lower extremities. Postural balance disorders are often a big problem for the elderly because they have a fear of falling which will cause fractures, even head injuries, all of which can hinder the elderly's daily activities and cause dependence to carry out activities. Objectives: The purpose of this community service is so that people know how to do balance exercises. This community service partner is the elderly in Rt 09 who has been given education and training. Result: After being given education, the participants' knowledge increased from 60% to 701%. After being given balance training, the average balance value before the intervention was 42.16 while after the intervention was 49.83 so that the average difference in the balance value before and after the intervention was 8. Conclusions: This proves that counseling activities and balance training in the elderly are important to prevent the risk of falling in the elderly.